THE EFFECT OF PROMOTION AND STORE ATMOSPHERE ON IMPULSE BUYING WITH SHOPPING EMOTION AS AN INTERVENING VARIABLE (EMPIRICAL STUDY OF MALL SKA PEKANBARU VISITORS) - Fadilah, Arief; Maulana, Hutomo Atman (Politeknik Negeri Bengkalis, 2024)
This study aims to determine the effect of promotion and store atmosphere on impulse buying with shopping emotion as an intervening variable at Mall SKA Pekanbaru. The method used in this study is a quantitative approach by collecting primary data through distributing questionnaires and secondary data through document. The samples in this study were people who had visited or shopped at the Mall SKA Pekanbaru. The sampling technique this study was purpossive sampling of 100 respondent. Processing data study uses Application SPSS Program 25. The results of this research show that promotion has a positive and significant effect on shopping emotion, Store atmosphere has a positive and significant effect on shopping emotion. Promotion has no positive and significant effect on impulse buying, store atmosphere has a positive and significant effect on impulse buying, and shopping emotion has a positive and significant effect on impulse buying. Then promotion has a positive and significant effect on impulse buying through shopping emotion as an intervening variable, which is followed by store atmosphere having a positive and significant effect on impulse buying through shopping emotion as an intervening variable.Keyword : Promotion, store atmosphere, shopping emotion, impulse buying